MORPHOLOGICAL AND FUNCTIONAL CHANGES OF MASTICATORY MUSCLE NEUROMUSCULAR JUNCTIONS IN THE LATER PERIODS OF STREPTOZOTOCIN DIABETES MELLITUS COURSE - Zhurakivska, O.Ya.; Grad, A.O.; Popel, S.L.; Zaiats, I.T.; Krynytska, I.Ya.; Marushchak, M.I.; Dzetsiukh, T.I. (World of Medicine and Biology, 2017)
The work is devoted to the study of morphofunctional changes of neuromuscular junctions (NMJ) and their hemocirculatory circulation in streptozotocin diabetes mellitus (SDM). Histological and electron microscopic methods of investigation were used. It was established that the SDM for 56-70 days of the course leads to the destruction of most NMJs, which is morphometrically expressed in the decrease of their area. In efferent preterminal nerve fibers, axonal atrophy occurs and partial degeneration of the myelin sheath. At the ultra-structural level, there is a violation of the fine architectonics of neuromuscular synapses, namely, a decrease in the area, the length of the synaptic contact, the number of synaptic vesicles, the number of folds of the postsynaptic membrane, and the distance between them. Such changes in NMJ occur on the background of the development of diabetic microangiopathy and, as a result, lead to a violation of the conductivity of nerve fibers in the masticatory muscle and the excitability of muscle fibers, as evidenced by the data of electroneuromyography of the ENMG. According to ENMG data, with the duration of experimental diabetes of 56-70 days, the axonal polyneuropathy was detected in 6 animals, the other 4 had an axonal-demyelinating polyneuropathy. In this case, only in 9.5% of cases the duration of the motor unit potentials decreases, but in 64.5% of cases the amplitude of the oscillations decreases (p
Keywords: neuromuscular junction; chewing muscle; streptozotocin diabetes mellitus